Optimization and characterization of fatty acid esters (FAES) based nanostructured lipid carrier (NLC) by Box-Behnken analysis - Sarah Shazwani S.,; Misni Misran, (Penerbit Universiti Kebangsaan Malaysia, 2022)
An unfavorable rate of toxicity and hydrophobicity of active substance in water has prompted the development of an improved active ingredients delivery systems such as nanostructured lipid carriers (NLC). This present study investigates varying components of NLCs compositions to achieve an optimized and stable colloidal suspension of NLCs through Box-Behnken design analysis for potential use as an active substance carrier system. The optimised formulation is comprised of 2.9% stearic acid, 0.4% MCT, 0.3% IPM, 0.37% Tween 20, 0.23% Span 20 and 96% deionised water (DW). The mean particle size, polydispersity index, and zeta potential of the optimized NLCs were 322±13.5 nm, 0.199±0.04, and -36±0.1 mV, respectively. Based on the TEM micrograph, NLCs can be observed as having an elongated spherical shape with a dense appearance.